A Framework for the Empirical Investigation of Mindfulness Meditative Development - Galante, Julieta; Grabovac, Andrea; Wright, Malcolm; Ingram, Daniel M.; Van Dam, Nicholas T.; Sanguinetti, Joseph L.; Sparby, Terje; van Lutterveld, Remko; Sacchet, Matthew D. (Mindfulness, 2023)
Millions of people globally have learned mindfulness meditation with the goal of improving health and well-being outcomes in both clinical and non-clinical contexts. An estimated half of these practitioners follow mindfulness teachers’ recommendations to continue regular meditation after completion of initial instruction, but it is unclear whether benefits are strengthened by regular practice and whether harm can occur. Increasing evidence shows a wide range of experiences that can arise with regular mindfulness meditation, from profoundly positive to challenging and potentially harmful. Initial research suggests that complex interactions and temporal sequences may explain these experiential phenomena and their relations to health and well-being. We believe further study of the effects of mindfulness meditation is urgently needed to better understand the benefits and challenges of continued practice after initial instructions. Effects may vary systematically over time due to factors such as initial dosage, accumulation of ongoing practice, developing skill of the meditator, and complex interactions with the subjects’ past experiences and present environment. We propose that framing mindfulness meditation experiences and any associated health and well-being benefits within integrated longitudinal models may be more illuminating than treating them as discrete, unrelated events. We call for ontologically agnostic, collaborative, and interdisciplinary research to study the effects of continued mindfulness meditation and their contexts, advancing the view that practical information found within religious and spiritual contemplative traditions can serve to develop initial theories and scientifically falsifiable hypotheses. Such investigation could inform safer and more effective applications of mindfulness meditation training for improving health and well-being.